Transcriptional Proposition for Uniquely Developed Protocorm Flowering in Three Orchid Species: Resources for Innovative Breeding - Ahmad, Sagheer; Chen, Jinliao; Chen, Guizhen; Huang, Jie; Hao, Yang; Shi, Xiaoling; Liu, Yuying; Tu, Song; Zhou, Yuzhen; Zhao, Kai; Lan, Siren; Liu, Zhongjian; et al. (Frontiers in Plant Science, 2022)
During orchid seed culture, seeds germinate as protocorms, and protocorms normally develop into plant with leaves and roots, and generally require many years of vegetative development for flowering. However, under certain combination of growth culture, we observed that protocorms can directly flower without leaves and roots. Therefore, we performed comparative transcriptome analysis to identify the different transcriptional regulators of these two types of protocorms of Cymbidium ensifolium, C. sinense and C. goeringii. Zinc finger, MYB, AP2 and bHLH were the most abundant TF families in the transcriptome. Weighted gene coexpression network analysis (WGCNA) was performed to identify hub genes related to leaf and flower development. The key hubs included SPL6, SVP, SEP2, KNOX1, AP2, OFP1, COL12, MYB13, MYB36, MYB59, bHLH086, and ARF7. The hub genes were further validated through statistical tools to propose roles of key transcription factors. Therefore, this study initiates to answer that why there is no leaf initiation and root development and how can protocorm bypass the vegetative development to flower? The outcomes can direct future research on short span flowering acquisition through protocorms.